IMPROVING STUDENTS’ WRITING SKILL OF RECOUNT TEXT THROUGH DIARY WRITING - Autila, Rani (TELL - US JOURNAL, 2017)
This research investigated the students’ writing skill on Recount Text at Session 2016 A English Department of STKIP PGRI West Sumatera. Some of them had difficulties in organization, content, grammar, mechanic, and vocabulary. Then, they really need lecturers’ guidance in every step of their writing process. Therefore, the independent writing should be applied in each part of their writing process. As consequence, the researcher applied Diary Writing as the focus of research to solve this problem. The purpose was to find whether Diary Writing can improve students’ writing skill on Recount Text. The method of research is a classroom action research (CAR).  This research was conducted in one cycle, which has six meetings. Researcher used writing test, observation checklist, and field note, as the instruments. The findings of the research showed that the students’ writing skill of Recount Text improved through Diary Writing. The implications related to this research, the lecturers are suggested to use Diary Writing to help students to be independent and creative writer and for the next researcher to use Diary Writing in others kinds of texts.